O currículo escolar do Colégio Estadual Casa Jovem - Silva, Diana Lícia Guerra dos Santos (2011)
With the intensive discussions about the field of education and education in the city new debates have been raised and new possibilities for curricular elements have been listed in an attempt to build theoretical and conceptual process of the training curriculum in the field. These new elements are present, especially, the contextuality of the field and their specificities, and differentiation of the urban context, and ecological issues. Thus, this paper seeks to put in question the characterization of the State College Youth House (infrastructure, staff, school projects, teachers), its history and its projects in the formation of an institution steeped in peasant reality.